Bone Marrow Plasma Cell Assessment before Peripheral Blood Stem Cell Mobilization in Patients with Multiple Myeloma Undergoing Autologous Stem Cell Transplantation - Lee, Sung-Eun (Hindawi Publishing Corporation, 2014)
The current definition of complete response (CR) in multiple myeloma (MM) includes negative serum and urine immunofixation (IFE) tests and <5% bone marrow plasma cells (BMPCs). However, many studies of the prognostic impact of pretransplant response have not included BMPCs. We evaluated the prognostic impact of BMPC assessment before peripheral blood stem cell (PBSC) mobilization on subsequent transplant outcomes. BMPCs were assessed by CD138, kappa, and lambda immunostaining in 106 patients. After a median followup of 24.5 months, patients with <5% BMPCs had a significantly better progression-free survival (PFS) compared to those with ≥5% BMPCs (P = 0.005). Patients with <5% BMPCs + serologic CR showed superior PFS compared to those with <5% BMPCs + serologic non-CR (P = 0.050) or ≥5% BMPCs + serologic non-CR (P = 0.001). Interestingly, the prognostic impact of BMPCs was more apparent for patients who did not achieve a serologic CR (P = 0.042) compared to those with a serologic CR (P = 0.647). We concluded that IFE negativity and <5% BMPCs before PBSC mobilization were important factors to predict PFS in patients with MM undergoing ASCT. Particularly, a significant impact of <5% BMPCs was observed in patients who did not achieve IFE negativity.